Cover Image, Volume 60, Issue 3. Issue 3 (17th February 2021) - Lu, Kai; Bhat, Madhavi; Peters, Sara; Mitra, Rita; Oberyszyn, Tatiana; Basu, Sujit
Abstract : The cover image is based on the Brief Communication Suppression of beta 2 adrenergic receptor actions prevent UVB mediated cutaneous squamous cell tumorigenesis through inhibition of VEGF‐A induced angiogenesis by Kai Lu et al., https://doi.org/10.1002/mc.23281 .